Liquefaction resistance of christchurch sandy soils from direct simple shear tests. Issue 141 (February 2021) - Cappellaro, Claudio; Cubrinovski, Misko; Bray, Jonathan D.; Chiaro, Gabriele; Riemer, Michael F.; Stringer, Mark E.
Abstract: A series of cyclic direct simple shear tests are performed to investigate the liquefaction resistance of sandy soils from Christchurch, New Zealand. The study focuses on the combined effects of soil density and fines content on liquefaction resistance of sandy soils. Two sands, a non-plastic silt, and their mixtures prepared at different fines contents are tested at two sets of relative densities. Test specimens are reconstituted using a procedure for water sedimentation, yielding soil fabric and soil structure resembling those of fluvial soil deposits. Differences are observed between the two host sands in the sensitivity of the cyclic liquefaction resistance to changes in relative density. Differences are also seen in the effects of the addition of fines to the liquefaction resistances of the two sands. Monotonic undrained direct simple shear tests are employed to explore an interpretation of the liquefaction resistance of the tested soils within the critical state framework. The state-concept interpretation provides more consistent quantification of the effects of initial state on the liquefaction resistance; however, the relationship between the state parameter and liquefaction resistance is soil dependent. The results of cyclic direct simple shear tests for soils containing up to 30% fines show reasonably consistent liquefaction resistances relative to estimates from empirical CPT-based liquefaction triggering relationships. Highlights: Cyclic undrained direct simple shear tests on Christchurch sandy soils. Tests to evaluate effects of non-plastic fines on liquefaction resistance. Specimens prepared by water sedimentation. Effects of addition of fines at given relative density depend on sand and fines. Liquefaction resistance may decrease or remain unchanged.